English Reading - Based Writing Model: A blended learning alternative - Rozimela, Yenni (Universitas Nusantara PGRI Kediri, 2021)
ABSTRACT Writing is often regarded as a difficult skill to acquire by majority of EFL learners. Teaching writing is also unquestionably challenging. It is argued that an essential effort to assist learners is having them explore information to write through reading topic and genre- related sources extensively. This article seeks to explain the result of a study employing R&D method to develop a Reading-Based Model to teach academic writing. It will report the results of the needs analysis briefly and then explain the model itself. The data about the students' needs of writing according to the students and the writing lecturers were collected through questionnaire and interview. The results of needs analysis and relevant literature confirmed that reading prior and during writing is elemental. The syntax of the model was developed on the basis of literature dealing with the principles of reading-writing relations and the Genre-based Approach. It consists of 4 main stages. Some activities within each stage can be carried out online. The model has gone through a validation process by two experts (two experienced lecturers teaching writing skills). The model was considered valid by the experts; a few recommendations were concerned with additional activities.